Adolescenza, sport, alimentazione Un caso di ricerca azione con strumenti antropologici - Cellini, Andrea (Antropologia Pubblica, 2024)
This is a project born from a group of formers pro athletes who founded the amateur sports association Élite Sport Academy, in order to respond to the development needs of the project’s recipients. The project targets students of the age group between eleven and eighteen and its purpose is to accompany the teenagers in their path of growth. In summary, the main object is to help them achieve a stable psycho-physical and aptitude well-being, through a path that includes a healthy diet, exercise and assisted study. During the design phase, the decision-making procedures have hinged on the centrality of the recipients and their families. They were considered both as active subjects and objects of the action promoted. One of the objectives is to make alliances with the people and institutions involved in the educational process of adolescents, meaning school, family and sports society, since these represent the educational community of the subject. During the research work the observation was implemented. Through team meetings a total supervision work was carried out to plan corrections. The relational modalities of the ESA staff in winning the confidence of teenagers have proved to be greatly effective for the task. Finally the publication of the results of the research, extremely positive, consolidated the authority of the ESA staff and the soundness of the project.